Ligand-Free Copper-Catalyzed Cross-Coupling Reaction of Alkynes with Aryl Iodides and Vinyl Halides - Tsai, Wan-Ting; Lin, Yun-Yung; Chen, Yi-An; Lee, Chin-Fa (Synlett, 2014)
A copper-catalyzed cross-coupling reaction of alkynes with aryl iodides is described. The system tolerates a broad range of functional groups and enables the sterically demanding substrates presented during the catalysis with only 5–10 mol% of Cu2O as the catalyst.
Keywords: copper; cross-coupling; Sonogashira reaction; ligand-free; aryl iodide; vinyl halide